SAREKAT DAGANG ISLAM : KEMANDIRIAN EKONOMI ISLAM DIBAWAH TEKANAN PEMERINTAH KOLONIAL BELANDA - Izzur Rozabi; Arif Hoetoro (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
Sarekat Dagang Islam is an organization that moves because of the suppression carried out by the Dutch colonial government. Starting from a market economy then moves to state politics. Sarekat Dagang Islam a threat to the Dutch colonial government so that they look at ways to weaken the Sarekat Dagang Islam. Ways in which the Dutch colonial government was to infiltrate western socialist thinking and doing politics pitting. Keywords : Sarekat Dagang Islam, Economy, Suppression, Dutch colonial government.